Childhood exposure to multiple persistent organic pollutants and midlife cognitive function - Wu, Feitong; Kartiosuo, Noora; Kaikkonen, Jari; Magnussen, Costan G.; Rantakokko, Panu; Kiviranta, Hannu; Pahkala, Katja; Hutri, Nina; Juonala, Markus; Viikari, Jorma S. A.; Raitakari, Olli T.; Rovio, Suvi P. (Elsevier, 2026)
Introduction
Whether early-life exposure to persistent organic pollutants (POPs) associates with adult cognitive function is unknown. We examined the association of childhood serum POPs levels with cognitive function in midlife.
Methods
This was a prospective cohort study of 1304 children aged 3–18 years. Childhood serum levels of 18 POPs including p,p′-dichlorodiphenyltrichloroethane (p,p′-DDT), p,p′-dichlorodiphenyldichloroethylene (pp′-DDE), pentachlorobenzene (PeCB), hexachlorobenzene (HCB), hexachlorocyclohexanes (HCHs), polychlorinated biphenyls (PCBs), trans-nonachlor were measured in childhood and early adulthoood. In mid-adulthood, cognitive function was measured using a computerized test battery (CANTAB) including tests for 1) memory and learning, 2) working memory, 3) reaction time, and 4) information processing. We assessed the overall association of the 18 POPs with cognitive function (normalized with mean 0 and standard deviation 1) by deriving a POP mixture index using weighted quantile sum (WQS) regression.
Results
For every unit-increase in the derived POP index (range 0–3, SD = 0.7), 0.129 (95% CI: −0.244, −0.014) SD-units lower memory and learning in midlife was observed when adjusting for covariates and adult POP index. This association was stable as shown by repeated holdout validation (β = −0.086, 95% confidence interval: −0.160 to −0.011), corresponding to 1.7 years additional aging on memory and learning. The POP mixture index was predominated by HCB (23%), p,p′-DDT (21%), PCB99 (10%), and p,p′-DDE (10%).
Conclusions
Childhood exposure to a high level of multiple POPs, such as HCB, p,p′-DDT and PCB99, was associated with poorer memory and learning in midlife, independent of adult exposure to those POPs.